Medial dorsal cutaneous nerve entrapment following inversion ankle sprain - Alves, Marcelo P. T.; Nóbrega, João P. G.; Dourado, Paulo F. F. M. (International Journal of Research in Orthopaedics, 2024)
The medial dorsal cutaneous nerve is one of the terminal branches of the superficial peroneal nerve that provides sensory innervation to the dorsum of the foot. It may be prone to injury by direct blow, iatrogenic surgical lesion or in rare situations secondary to ankle sprains. The authors report a case of persistent ankle pain in a female patient caused by a post- traumatic compressive neuropathy of the medial dorsal cutaneous nerve secondary to an ankle sprain which was successfully surgically treated with complete resolution of the symptoms.